Genetic diversity of Avena strigosa Schreb. ecotypes on the basis of isoenzyme markers - Kubiak, Katarzyna (Biodiversity: Research and Conservation, 2010)
Genetic diversity was analyzed in 19 ecotypes of the diploid oat A. strigosa originating from various geographical regions of the world. Six isoenzyme systems (AAT, ACP, EST, LAP, MDH, PX) were studied and 16 loci were identified. Only two loci (Est4 and Mdh2) were polymorphic. Ecotypes were characterized by the percentage of polymorphic loci (P=3.3%), the mean number of alleles per locus (A=1.04) and intrapopulation diversity (HS=0.013). Total genetic diversity (HT=0.07) and interpopulation diversity (DST=0.057) were examined as well. The value of the coefficient of gene differentiation (GST=0.821) indicated that diversity among populations was an important contributor to total variability. Genetic similarity between A. strigosa populations was very high (IN=0.94). Cluster analysis did not demonstrate strongly differentiated groups among the ecotypes examined.